The Mediating Effect of Perceived Behavioral Control in the Relationship between Participation Intention and Practice Effect in Educational Practice - Kang, Yu; Lay, Yoon Fah (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2025)
Many researches have been carried out in the aspects of management and organization, preparation, implementation, summary and evaluation of educational practice, but there is no in-depth research on the students’ behavior in the process. However, students' own problems, such as attitude, frustration ability, adaptability to the new environment and family factors, all affect the educational practice effect, greatly hinder the improvement of students' teaching skills, which is the basic quality of qualified teachers, and are not conducive to students' career development and lifelong growth. This research is from the perspective of students who participate in educational practice, focuses on analyzing the relationship between students' perceived behavioral control, participation intention and practice effect used PLS-SEM. A pilot study was conducted with 60 students to test the reliability and validity of the instruments. Subsequently, 200 students who had completed the educational practice were selected for actual research through purposeful and random sampling. The results indicated that perceived behavioral control and participation intention positively predict the practice effect, as well as participation intention mediates the relationship between perceived behavioral control and practice effect. This current research offered theoretical support and practical suggestions for the educational practice, and education administrators can better adjust and improve education policies, so as to promote the improvement of teacher education quality, further promote educational curriculum reform.